Heart morphology and function evaluation by transthoracic echocardiography in six captive crested gibbons (Nomascus spp.) - Irène Vonfeld; Anaïs Nowakowski; Brice Lefaux; Benoît Quintard (Revue de Primatologie)
Cardiovascular diseases are one of the leading causes of morbidity and mortality in captive apes. Transthoracic echocardiography is the most comprehensive cardiovascular imaging technique used to diagnose and monitor cardiopathies in mammals. However, there are currently no baseline data of heart morphology and function in hylobatid primates. Conventional transthoracic echocardiograms were performed on six clinically healthy crested gibbons of three species (Nomascus siki, N. leucogenys and N. gabriellae) under general anesthesia using sevoflurane without premedication. Each echocardiogram included the evaluation of 11 variables in bidimensional mode, 8 variables in M-Mode and 6 variables in Doppler mode. Most functional parameters evaluated, like left ventricular ejection fraction (range, 49.3 to 72.4%), shortening fraction (SF; range, 18.9 to 34.5%), left atrium/aorta ratio (range, 0.8 to 1.2), and maximal velocity of aortic, pulmonic, and mitral flows had similar values as those described in gorillas, dogs, and humans. Valvular insufficiencies were detected in two of the six individuals evaluated: one adult female N. siki was diagnosed with a discrete aortic regurgitation and one young male N. leucogenys with a mild mitral valve insufficiency. The mitral valve regurgitation was associated with a low-grade systolic heart murmur, but no further morphological changes of heart chambers were identified in these animals. Finally, a decreased heart contractility (SF = 18.9%) was diagnosed in one female N. gabriellae. This study is the first database transthoracic echocardiography in gibbons undergoing general anesthesia.